1996
DOI: 10.3346/jkms.1996.11.2.171
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the surgical procedures to treat advanced Kienbock's disease

Abstract: We have treated a total of 16 cases of advanced Kienböck's disease, stage III and IV by Lichtman's classification, with triscaphe fusion, tendon ball replacement arthroplasty after excision of lunate, proximal row carpectomy as a salvage procedure and limited wrist fusion, since 1985. All cases were followed for minimal 16 months after each operation. Tendon ball replacement arthroplasty after excision of lunate could not prevent further carpal collapse with persistent chronic wrist pain. The triscaphe fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…There was 1 failure (8%) requiring arthrodesis at 3 years. In terms of comparative studies, Rhee et al 39 and Nakamura et al 6 have reported on PRC versus limited wrist arthrodesis for stage III and IV Kienböck's disease with conflicting results. Rhee et al found end results of PRC much better than those of limited arthrodesis at 16 months of follow-up, whereas Nakamura found more satisfactory results at an average of 5 years after scaphotrapezio-trapezoidal joint arthrodesis than after PRC.…”
Section: Discussionmentioning
confidence: 98%
“…There was 1 failure (8%) requiring arthrodesis at 3 years. In terms of comparative studies, Rhee et al 39 and Nakamura et al 6 have reported on PRC versus limited wrist arthrodesis for stage III and IV Kienböck's disease with conflicting results. Rhee et al found end results of PRC much better than those of limited arthrodesis at 16 months of follow-up, whereas Nakamura found more satisfactory results at an average of 5 years after scaphotrapezio-trapezoidal joint arthrodesis than after PRC.…”
Section: Discussionmentioning
confidence: 98%
“…2,3 Long-term follow-up evaluation, however, has noted that removal of the lunate alone leads to proximal migration of the capitate, precipitating poor results. [3][4][5] Filling the empty space with a silicone rubber implant has been reported 2,6 but silicone is collapsible and incapable of supporting any but the lightest of wrist loads. Its placement into the lunate's defect therefore does not have any meaningful biomechanical significance.…”
mentioning
confidence: 99%
“…The term 'advanced Kienbock's Disease' [1,8,11,14] has been used in many articles but there is no clear definition or [12,14,16] and wrist fusion [9]. There is no strong evidence to support the use of one procedure over the other.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al [8] and Rhee et al [11] compared limited carpal fusions with proximal row carpectomy. Rhee et al [11] concluded that the overall results of proximal row carpectomy are better then any carpal arthrodesis (STT fusion with lunate excision) though the ideal treatment of advanced Kienbock's depends on the patient's age, sex, job and the stage of disease. Nakamura et al [8] had a mixture of limited carpal fusions in their series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation